Che Guevara : you win or you die - Kallen, Stuart A., 1955- (Twenty-First Century Books, 2013)
A biography of Argentinean revolutionary leader, Che Guevara, discussing how he became a rebel leader and created an anti-capitalist movement, came to help overthrow the Cuban dictatorship in 1959, and his assassination by the Bolivian army and the world's reaction.